PENGARUH KONSENTRASI MALTODEKSTRIN TERHADAP KARAKTERISKTIK FISIKOKIMIA SERBUK EKSTRAK BUAH PARIJOTO (Medinilla speciosa Blume) - Maslikhatul Ummah; Bambang Kunarto; Ery Pratiwi (Jurnal Teknologi Pangan dan Hasil Pertanian, 2021)
The purpose of this research is to know the effect of increasing the concentration of maltodextrin on the physicochemical characteristics of parijoto fruit (Medinilla speciosa Blume) extract powder by analyzing yield, solubility, color intensity, air content, and anthocyanin content. The experimental design used in this study was a Completely Randomized Design (CRD) with one factor and 3 replications. The studied factors were the concentration of maltodextrin in making powder from parijoto fruit extract which consisted of 6 treatments, they are: 5%, 10%, 15%, 20%, 25%, and 30%. If there is a significant difference between treatments, further testing is carried out with the Duncan test at 5% level. The results showed that the addition of maltodextrin had a significant effect on all parameters of parijoto fruit extract powder. The best anthocyanin powder from parijoto fruit extract was the concentration of maltodextrin 10%, anthocyanin content 2.68 ppm, yield 12.48%, solubility 79.96%, water content 4.22%, lightening level (L*) 55.05, redness level (a*) 18.10, and yellowness level (b*) 16.64.